A hybrid electronic nose system for discrimination of pathogenic bacterial volatile compounds. Issue 47 (23rd November 2020) - Seesaard, Thara; Thippakorn, Chadinee; Kerdcharoen, Teerakiat; Kladsomboon, Sumana
Abstract : Self-built hybrid electronic nose prototypes equipped with organic–inorganic nanocomposite gas sensors and metal-oxide semiconductor gas sensors for bacterial discrimination. Abstract : A hybrid electronic nose comprising an array of three organic–inorganic nanocomposite gas sensors [zinc tetra tert -butyl phthalocyanine (ZnTTBPc), zinc tetra-phenyl porphyrin (ZnTPP), and cobalt tetraphenyl-porphyrin (CoTPP)] coupled with three commercial metal-oxide semiconductor gas sensors (TGS 2444, TGS 2603 and TGS 2620) was developed to discriminate bacterial volatile compounds. Each type of gas sensor had its own strengths and weaknesses in terms of its capability to detect complex odors from the five different bacterial species tested. Bacterial samples were controlled at a fixed initial bacterial concentration by measuring the optical density at 600 nm of the culture suspensions. A comparative evaluation of the volatile compound fingerprints from five bacterial species grown in Luria–Bertani medium was conducted to identify the optimal incubation time for detection of volatile biomarkers to discriminate among bacteria. The results suggest that the hybrid electronic nose was indeed able to discriminate among the bacterial species and culture media, with a variance based on contributions of 92.4% from PC1 and 7.2% from PC2, at an incubation time of 6 hours. Furthermore, the results of hierarchical cluster analysis showed that bacterial odor data formed two major bacterial groups, with the maximum cluster distance close to 25. Intra-group similarity was demonstrated as the two bacterial species ( E. cloacae and P. aeruginosa ) from among the Gram-negative bacteria had a greater similarity with a cluster distance close to 4. Finally, the minimum distance between E. cloacae and S. Typhi was approximately 1, at an equal distance from E. coli and S. aureus .